On Volterra inequalities and their applications - Lechosław Hącia (International Journal of Mathematics and Mathematical Sciences)
We present certain variants of two-dimensional and n-dimensional Volterra integral inequalities. In particular, generalizations of the Gronwall inequality are obtained. These results are applied in various problems for differential and integral equations.